The Impact of Hospital Service Technology and Service Quality on Patient Revisit Intention: Mediating Role of Patient Experience - Priyanto, Eko Budi; Euis Rahayuningsih; Sarfilianty Anggiani (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study investigates the synergistic influence of hospital service technology and service quality on patient experience, and how this experience subsequently affects revisit intention. Drawing on data from 195 patients across one public and four private hospitals in Tangerang, Banten Province, the research employs partial least squares structural equation modeling (PLS-SEM) to test a conceptual framework integrating technological and human-centric service dimensions. Results indicate that both hospital service technology and service quality significantly enhance patient experience, which in turn strongly influences revisit intention. The mediating role of patient experience is also confirmed, with indirect effects showing that improvements in both technology and service quality translate into greater patient loyalty through enhanced experiential outcomes. These findings suggest aligning technological advancements with fundamental service excellence to foster long-term patient relationships. Theoretical and practical implications are discussed, highlighting strategies for healthcare providers aiming to improve patient retention and institutional reputation in an increasingly competitive environment.